Engaing Brand Awareness for Sustainable Innovations in Cultural Tourism Towards Intangible Cultural Heritage (ICH): The Case Studies of China, Myanmar, Thailand, and Australia - Ousanee Sawagvudcharee (Revista de Gestão Social e Ambiental, 2024)
Purpose: This research aims to improve our understanding of the development of intangible cultural heritage with the goal of promoting cultural tourism along with sustainable innovations that prioritize sustainable and environmentally conscious locations. This will be done by using brand awareness to develop sustainable innovations for cultural tourism through intangible cultural heritage. Theoretical Framework: The study of sustainable innovations in cultural tourism through intangible cultural heritage focuses on raising awareness and promoting green tourism towards knowledge cybernetics (KC). This is done in order to promote tourism culture by raising brand awareness through intangible cultural heritage for sustainable innovations that draw some identities from intangible cultural heritages. Method: Philosophy, ontological, and epistemological stances, the interpretative approach, a case study methodology, the research design specification, the ethics of human research, and the rationale for the qualitative research methodology employed in this study are all highlighted in the study. As a case study methodology, an interpretive approach was used. The qualitative perspective and the triangulation method were supported by both documentation analysis and non-participation observation. Critical analyses, thematic coding, and content analysis were used to examine the data. Results and Discussion: According to the results, brand awareness plays a significant role in developing sustainable innovations towards intangible cultural heritages for cultural tourism, which in turn encourages and stimulates travelers to pay attention to a place and be inclined to return. Additionally, it should assist travel destinations in consistently receiving viral marketing and a range of word-of-mouth referrals. Research Implications: This practical study uses 4 countries—China, Myanmar, Thailand, and Australia—as the case studies to illustrate the importance of building brand awareness towards intangible cultural heritages for sustainable innovations to promote cultural tourism. It should demonstrate their importance to community development, local and national economics, the preservation and propagation of intangible culture, and the establishment of long-term jobs and revenue streams for the local population.
Keywords: Sustainability and Innovation in Business; Diverse Aspects of Tourism Research; Digital Marketing and Social Media